Construction Of Growth Band For Early Selection Of Indigenous Pigs In India (Applied Biological Research, 2013)
The present study conducted at the Institute Farm of National Research Centre  on Pig, Guwahati (Assam) was aimed to assess the pre-weaning growth pattern  and construct growth band in ‘Ghungroo’ and ‘Niang Megha’ pigs maintained  under standard breeding, feeding and management conditions. Piglets of both  breeds were maintained under similar management conditions with creep feed  costing Rs. 15.76 kg-1amounting to Rs. 46.35 upto weaning age (56 days). The  overall mean weight at birth and weaning was 0.96±0.02 and 7.07±0.26 kg,  respectively, for ‘Ghungroo’ pig and 0.64±0.02 and 5.47±0.13 kg, respectively,  for ‘Niang Megha’ pig. The growth curves were linear for all the cases with  accuracy of prediction ranging between 97.6 and 99.5%. Breeds of animal  showed highly significant difference in body weight for all the weeks. The growth  band developed can be used for early selection of animals.
Keywords: Body weight; Ghungroo; growth rate; Niang Megha; pigs